From Kitchen Waste to Climate Solution A P5 Project of SMA POMOSDA - Saatun Nuzuliyah; Suci Hidayati (Proceeding International Conference on Digital Education and Social Science, 2024)
This study aims to investigate the potential of Eco-enzyme production as an effective strategy to integrate climate change awareness into education sustainability practices. Eco-enzymes, fermented solutions derived from organic waste, offer a sustainable and cost-effective approach to waste management and environmental conservation. The P5 project involved a comprehensive approach including, educating students about climate change. It guides students in the production of Eco-enzymes using readily available organic waste materials, tracking the production process, measuring the quality of Eco-enzymes, and assessing their effectiveness in various applications, such as cleaning, composting, and pest control. It is also evaluating the environmental and social impact of Eco-enzyme production, including waste reduction, resource conservation, and community engagement. The results demonstrate that Eco-enzyme production can significantly reduce organic waste, improve soil fertility, and contribute to a cleaner environment. Moreover, the project has fostered a sense of environmental responsibility among students and community members, promoting sustainable behaviors and practices. In the end, it can integrate Eco-enzyme production into educational and organizational strategies. It will play a crucial role in addressing climate change and promoting sustainability. By empowering individuals to take action, we can collectively contribute to a greener and more resilient future.